Dimensi Mutu Layanan Persalinan Normal dan Kepuasan Ibu Bersalin di Bidan Praktek Swasta (BPS) - Elliana, Dewi; Kurniawati, Titik (Jurnal Promosi Kesehatan Indonesia, 2010)
Success of health development that felt is a reach expansion that optimally relative health service .The big challenge who gift health service is quality health service expectation in community. This research includes a descriptive by approaching survey. Research population is 25 mothers who give a birth on April 2009. Sample amount 25 mothers who give a birth on April 2009. The gathered data in his research is the primary and secondary data, by the use of questioner. This research obtained quality dimension of normal childbirth towards mothers satisfaction performance 52 % in good category, greatness 60 % in good category, responsiveness 88 % in good category, Assurance 64 % in good category, empathy 72 % in good category and 28 % in less category.